INSERTED CONSTRUCTIONS IN A. N. RADISCHEV’S NOVEL "JOURNEY FROM PETERSBURG TO MOSCOW" - Irina Yurievna Kononova (Galaxy International Interdisciplinary Research Journal, 2023)
This paper describes the functioning of parentheticals as a means of switching between different functional and semantic layers of the text; the following types of insertions are distinguished: parenthetical remarks, metalinguistic, causative, and evaluative parentheticals.